International Humanitarian Law at the Crossroads: A Strategic Reflection on the Failure of Civil Protection in the Russia-Ukraine Conflict - Aritonang, RH; Sujiwo, Aji; Susilo, Tarsisius; Tadung, Rapy; Panggabean, Andar Dodianto (Balobe Law Journal, 2025)
Introduction: This article analyzes the application of international humanitarian law (IHL) in the Russia–Ukraine conflict, focusing on the impact of hybrid warfare on civilian protection mechanisms.Purposes of the Research: The purpose of this article is to evaluate the failure of civilian protection during the Russia–Ukraine conflict from legal, ethical, and strategic perspectives.Methods of the Research: This research uses a qualitative normative method, employing case study and literature review approaches, supported by interviews with legal practitioners to explore gaps between IHL norms and military operations.Results of the Research: The findings of this study show a critical disjunction between IHL provisions and military practices on the ground, leading to significant risks for non-combatants. The hybrid nature of the conflict complicates legal accountability and ethical compliance. This article offers a novel recommendation for reformulating combat strategies and updating military education curricula to better internalize IHL principles in contemporary armed conflicts.